Polyculture of freshwater prawn (Macrobrachium rosenbergii) with some indian major carps in coastal earthen ponds of Bagerhat (Journal of the Sylhet Agricultural University, 2025)
The goal of the study was to assess the productivity and growth of polyculture prawn and carps cultivation at various stocking ratios in Bagerhat district over a four-month period from April to July 2022. Three treatments based on stocking ratios and three repetitions were employed in the randomized block design (RBD) experiment. Fingerlings of major carps (Catla catla, Labeo rohita, and Cirrhinus mrigala) and prawn (Macrobrachium rosenbergii) post larvae in T1, T2, and T3 were provided in the following ratios such as 3:1:1:1, 4:1:1:1, and 5:1:1:1, respectively. Both prawns and carps received daily meals consisting of both commercially prepared feeds and formulated feeds made on the farm. Recorded water quality were found to be within acceptable levels for prawn production and to not exhibit significant variations (p